Effect of Different Dosage Frequency of Polymyxin B on Rat Nephrotoxicity - Sun W; Hu B; Zhang X; Wang Y; Xiang Z; Lin G (Dove Medical Press, 2021)
Wenrui Sun,1,* Binchuan Hu,2,* Xiaoshan Zhang,1,3 Yuzhen Wang1 1,3 Zheng Xiang,3 Guanyang Lin1 1The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, 325000, People’s Republic of China; 2Yongjia People’s Hospital, Wenzhou, 325100, People’s Republic of China; 3Wenzhou Medical University, Wenzhou, 325000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Guanyang LinThe First Affiliated Hospital of Wenzhou Medical University, Nanbaixiang Street, Wenzhou, 325000, People’s Republic of ChinaTel/Fax +86 105 557 9706Email 13867702133@163.comBackground: Polymyxin B, as the final treatment against multidrug-resistant Gram-negative bacilli, is widely used in clinical practice. However, little is known about the nephrotoxicity of polymyxin B. The purpose of this study was to elucidate the relationship between polymyxin B nephrotoxicity and daily administration frequency.Methods: Sprague–Dawley rats were randomly divided into three groups: 18 mg/kg/q24 h group (Group A, once daily), 9 mg/kg/q12 h group (Group B, twice daily), and normal saline control group (Group C). The rats were injected subcutaneously for 5 consecutive days with the same daily total dose and different frequency of administration. The serum creatinine (SCr) and blood urea nitrogen (BUN) of each group before administration (0 h), and 8 and 24 h after administration, were measured by tail vein blood sampling. On the sixth day, the rats in each group were killed, the left kidney was taken for pathological section observation, and the results of each group were compared.Results: After 96 h of administrated polymyxin B, the total average level of SCr in Group A was 56.98± 12.42 μmol/L, that of Group B was 52.02± 8.68 μmol/L, and that of Group C was 34.36± 5.39 μmol/L. BUN was 9.86± 4.58, 10.54± 4.08, and 3.55± 0.73 mmol/L in Groups A, B, and C, respectively. The daily urinary protein excretion was 5004.45± 1333.84 μg in Group A, 4608.04± 1444.42 μg in Group B, and 2096.33± 215.28 μg in Group C. In addition, according to the observation of pathological slices, compared with Group A, the number of exfoliated and necrotic cells of renal tubules in Group B was higher, and the morphological changes were more serious.Conclusion: The experimental results showed that the renal toxicity in rats treated with a twice-daily subcutaneous dose of polymyxin B was higher than that in rats treated with once-daily dose of polymyxin B.Keywords: polymyxin B, dose, frequency, renal, nephrotoxicity